About Innovative Content of Subject-Oriented Pedagogical Education - R. M. Asadullin (Высшее образование в России)
The continuous modernization of the education system makes the problems of the quality of teacher training increasingly relevant. Moreover, the measures taken to improve the system of teacher education are largely confined to the introduction of new organizational and managerial mechanisms and practically do not affect the internal content and technological structure of the teacher training process.Modern pedagogical universities are constantly looking for innovative models of training teachers that will be able to solve non-standard social and professional tasks. However, recent studies in this area do not fully take into account the nature of pedagogical activity and conditions of its formation. Thus, the need arises for a special study of the processes and means of updating the content and technologies of teacher training in order to control the level of students’ professional competencies development, as required by educational and professional standards. This means the creation of a special educational system in a pedagogical university, which can provide a harmonious and synchronous mastering by future specialists of both subject knowledge and methods of pedagogical activity.The article provides a theoretical study aimed at identifying key patterns of designing a new content for teacher education, the basis of which is the formation of a future teacher as a subject of his own professional activity. The author describes the experience of using a subject-oriented model of education, implemented at Bashkir State Pedagogical University n.a. M. Akmulla. The effectiveness of this model is confirmed by the high level of students’ mastery of designing methods and constructing the educational process, as well as their positive experience in the implementation of educational activities.